1995
DOI: 10.1113/jphysiol.1995.sp020504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creatine phosphate and P(i) on Ca2+ movements and tension development in rat skinned skeletal muscle fibres.

Abstract: 1. Mechanically skinned fast-twitch (FT) and slow-twitch (ST) muscle fibres of the rat were used to investigate the effects of fatigue-like changes in creatine phosphate (CP) and inorganic phosphate (Pi) concentration on Ca2+-activation properties of the myofilaments as well as Ca2+ movements into and out of the sarcoplasmic reticulum (SR). 2. Decreasing CP from 50 mm to zero in FT fibres increased maximum Ca2+-activated tension (Tmax) by 16 + 2 % and shifted the mid-point of the tension-pCa relation (pCa50) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
219
1
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(248 citation statements)
references
References 32 publications
23
219
1
5
Order By: Relevance
“…Increasing the phosphate content of the medium had an effect on [Ca 2+ ] M increase or Ca 2+ release from mitochondria only when it reached the near-millimolar range, as expected from the solubility of the CaHPO 4 complex in ionic solutions or in other cellular compartments such as the endoplasmic reticulum (16). Our data strongly contrast with those obtained with fluorescent dyes such as fura2-FF in purified mitochondrial preparations [6,7], which showed much lower maximum free [Ca 2+ ] values (below 5 M) in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the phosphate content of the medium had an effect on [Ca 2+ ] M increase or Ca 2+ release from mitochondria only when it reached the near-millimolar range, as expected from the solubility of the CaHPO 4 complex in ionic solutions or in other cellular compartments such as the endoplasmic reticulum (16). Our data strongly contrast with those obtained with fluorescent dyes such as fura2-FF in purified mitochondrial preparations [6,7], which showed much lower maximum free [Ca 2+ ] values (below 5 M) in the mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31] Phosphate ion applied intracellularly or extracellularly to myofiber cells enters the sarcoplasmic reticulum and precipitates calcium, which in turn decreases muscle contraction. 32,33 Thus, sodium phosphate injections into muscle could somehow aid the entry of plasmid DNA into muscle cells. It has been reported that calcium is required for cell membrane resealing by a process involving recruitment of intracellular membrane vesicles which bind to, fuse with and patch damaged plasmalemma.…”
Section: Discussionmentioning
confidence: 99%
“…También se ha encontrado aumento del fosfato (P i ) libre durante el desarrollo de la fatiga y esto parece favorecer el depósito de Ca 2+ dentro del retículo sarcoplásmico en la forma de fosfato de Ca 2+ , lo cual disminuye el Ca 2+ disponible para ser liberado (115,116). Además, el aumento de P i causa disminución de la sensibilidad del mecanismo contráctil al Ca 2+ para generar tensión (86,100).…”
Section: El Aumento Del Mg 2+unclassified